What Is Lean Management in Health Care? Development of an Operational Definition for a Cochrane Systematic Review. Issue 3 (September 2019) - Rotter, Thomas; Plishka, Christopher; Lawal, Adegboyega; Harrison, Liz; Sari, Nazmi; Goodridge, Donna; Flynn, Rachel; Chan, James; Fiander, Michelle; Poksinska, Bonnie; Willoughby, Keith; Kinsman, Leigh
Industrial improvement approaches such as Lean management are increasingly being adopted in health care. Synthesis is necessary to ensure these approaches are evidence based and requires operationalization of concepts to ensure all relevant studies are included. This article outlines the process utilized to develop an operational definition of Lean in health care. The literature search, screening, data extraction, and data synthesis processes followed the recommendations outlined by the Cochrane Collaboration. Development of the operational definition utilized the methods prescribed by Kinsman et al. and Wieland et al. This involved extracting characteristics of Lean, synthesizing similar components to establish an operational definition, applying this definition, and updating the definition to address shortcomings. We identified two defining characteristics of Lean health-care management: (1) Lean philosophy, consisting of Lean principles and continuous improvement, and (2) Lean activities, which include Lean assessment activities and Lean improvement activities. The resulting operational definition requires that an organization or subunit of an organization had integrated Lean philosophy into the organization's mandate, guidelines, or policies and utilized at least one Lean assessment activity or Lean improvement activity. This operational definition of Lean management in health care will act as an objective screening criterion for our systematic review. To our knowledge, this is the first evidence-based operational definition of Lean management in health care.